Construção e manipulação de clone infeccioso de uma amostra brasileira do vírus da diarreia viral bovina - Arenhart, Sandra (2012)
Bovine viral diarrhea virus (BVDV) is a worldwide pathogen associated with important losses to livestock production. Most of these losses come from reproductive disorders and from the ability of the virus to produce persistent infections following in utero infection of the fetus. A number of reverse genetics methodologies have been used for BVDV in order to better understand the biology of the virus, which allowed the elucidation of a number of biological features including virus replication, host-virus interaction, immune response, and the pathogenesis of fetal infection. The present study describes the construction, characterization and manipulation of an infectious clone out of a non-cytophatic Brazilian BVDV strain IBSP4-ncp. The cDNA recombinant clone was constructed by yeast homologous recombination with a low-copy vector, from three genomic fragments comprising the open reading frame (ORF). The two untranslated regions (5' and 3' UTR) were replaced by the respective UTRs of the reference strain NADL. The constructed vector was transcribed in vitro and the resulting RNA was transfected on MDBK cells to rescue infectious virus. The rescued viruses (IC-pBSC_IBSP4-ncp#2 and #3) were maintained for ten passages in tissue culture and characterized in vitro, showing replication dynamics, focus size and morphology similar to those of the parental IBSP-4. Genomic analysis revealed five point mutations in the gene coding for Npro protein, resulting in amino acid changes. These mutations probably reflect an adaptation of the virus to the heterologous UTRs. The infectious clone IC-pBSC_IBSP4-ncp#2 was further used for the construction of a recombinant virus expressing the Gaussia luciferase (Gluc) reporter gene. The reporter gene was inserted between the Npro and Core genes, being flanked by an upstream linker and a downstream sequence of the Foot and Mouth Disease virus protease (FMDV2Apro) for accurate protein processing. The recombinant vector was in vitro transcribed and the RNA was transfected on MDBK cells. Recombinant infectious viruses were rescued (IC-pBSC_IBSP4-ncpGluc#3 and #4) and characterized in vitro, showing replication dynamics, focus size and morphology similar to those of the parental IBSP-4 clone. The Gluc reporter gene was accurately expressed and processed by the recombinant virus during 15 passages in tissue culture. These studies revealed that the infectious clone constructed herein can be easily manipulated and is able to carry in its genome heterologous genes up to 555 base pairs in length in a stable fashion and without interference with its replication efficiency. Thus, the constructed clone may be very useful for genetic manipulation towards studying different aspects of the BVDV biology and its interactions with the host, and for the development of vaccine strains with attenuated phenotype and/or with antigenic markers.